Penguatan Ketahanan Pangan Keluarga Melalui Kreasi Kue Tradisional Di Masa Pandemi Covid 19 Di Desa Punggur Kecil Kecamatan Sungai Kakap - Fatmawati; Syarmiati; Syarifah Ema Rahmaniah; Rizki Ratna Paramita; Basuni (Yayasan Kajian Riset dan Pengembangan RADISI, 2022)
Essentially, the involvement of housewives in processing food ingredients into food has become a habit. Housewives’ skills to process food ingredients into food have added value to the food itself. However, all this depends on their determination to avoid food vulnerability. The target of the community service activities of the Student Creativity Program of the Faculty of Social and Political Sciences (PKM Fisip) of the Tanjungpura University, is the joint activities of the Women’s Family Welfare Program (PKK) and the Women’s Qur’anic Study Congregation (Majelis Taklim). This can be seen in the activities of the housewives in Punggur Kecil Village of Sungai Kakap Sub-District. Various types of food that can be processed into traditional cakes come from their own farms such as crop plants that can be processed into foods that have a high nutritional value, delicious taste and assured cleanliness. The housewives’ ability to process food to sell can increase family income.